2019
DOI: 10.1002/adom.201901627
|View full text |Cite
|
Sign up to set email alerts
|

Improving Processability and Efficiency of Resonant TADF Emitters: A Design Strategy

Abstract: A new design strategy is introduced to address a persistent weakness with resonance thermally activated delayed fluorescence (R-TADF) emitters to reduce aggregation-caused quenching effects, which are identified as one of the key limiting factors. The emitter Mes 3 DiKTa shows an improved photoluminescence quantum yield of 80% compared to 75% for the reference DiKTa in 3.5 wt% 1,3-bis(N-carbazolyl)benzene. Importantly, emission from aggregates, even at high doping concentrations, is eliminated and aggregation-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
303
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 235 publications
(348 citation statements)
references
References 25 publications
(22 reference statements)
15
303
0
Order By: Relevance
“…The E ox and E red determined from the DPV peak Scheme 1 Synthetic route for DDiKTa. values are 1.63 and À1.27 V, respectively, showing the expected decreased DE due to increased conjugation compared to those of DiKTa (E ox : 1.65 eV; E red : À1.33 eV vs. SCE; determined from the DPV in MeCN), 21 a trend that is consistent with the DFT calculations. The UV-vis absorption, fluorescence and phosphorescence spectra of DDiKTa in dilute toluene solution are depicted in Fig.…”
Section: Photophysical Propertiessupporting
confidence: 83%
See 1 more Smart Citation
“…The E ox and E red determined from the DPV peak Scheme 1 Synthetic route for DDiKTa. values are 1.63 and À1.27 V, respectively, showing the expected decreased DE due to increased conjugation compared to those of DiKTa (E ox : 1.65 eV; E red : À1.33 eV vs. SCE; determined from the DPV in MeCN), 21 a trend that is consistent with the DFT calculations. The UV-vis absorption, fluorescence and phosphorescence spectra of DDiKTa in dilute toluene solution are depicted in Fig.…”
Section: Photophysical Propertiessupporting
confidence: 83%
“…19,20 We showed that by decorating a MR-TADF emitter, DiKTa, with mesityl groups, Mes 3 DiKTa, undesired aggregation caused quenching and excimer emission can be largely mitigated. 21 Herein, we report the emitter DDiKTa, which is a dimeric compound consisting of two MR-TADF DiKTa units (Scheme 1). The slightly increased conjugation present in DDikTa compared to DiKTa contributes to a modest red-shifting of the emission; however, the new compound conserves its MR-TADF status.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in 2020, Zysman‐Colman and co‐workers designed and synthesized a molecule based on a fused amine/carbonyl system. [ 117 ] Due to the opposite resonance effect of a nitrogen and oxygen atom in Mes 3 DiKTa (see Figure 12), the HOMO and LUMO were separated, resulting in a small Δ E ST (0.26 eV). Excellent OLED device performance was realized with an EQE of 21.1%, sky‐blue EL emission at 480 nm, and an FWHM of 37 nm.…”
Section: Emitters For Application In Oledsmentioning
confidence: 99%
“…[5][6][7][8] This contradiction undoubtedfully sets an obstacle to obtain highly efficient emitter, and the large structural reorganization occurred in the excited state would cause broad emission spectra and increased nonradiative decay channels, eventually weakening the performances of corresponding devices. [9][10][11][12][13][14][15] Instead of the conventional D-A configured emitters, a unique category of multiresonance TADF (MR-TADF) molecules based on fused polycyclic aromatics was lately proposed by Hatakeyama et. al.…”
mentioning
confidence: 99%
“…two magnitudes higher than DABNA (9.9×10 3 s -1 ) recorded at the same condition, indicating efficient tripletharvesting that might involve upper excited states (Table S1). [9,21,24] These represented promising characteristics of TADF dye for fabricating OLED with high performance. The suitable energy cascade between functional layers as well as ideal charge carrier injection of the emitter ensured relatively low turn-on voltages (Von, at 1 cd m -2 ) below 3.5 V for both devices (Fig.…”
mentioning
confidence: 99%